ORGANOLEPTIC AND PHYSICOCHEMICAL CHARACTERISTICS OF CONVENTIONAL AND MICROWAVE PROCESSING OF SATAY KOMOH FROM MEAT OF THUNNUS SP. STORED FROZEN AT VARIOUS MEAT DONENESS - Hardoko; Djamaludin H.; Tristany B.J. (Russian Journal of Agricultural and Socio-Economic Sciences)
Satay as a traditional Indonesian product is still sold directly in fresh processed form and none has been sold in frozen processed form. So far, various types of satay have been found based on raw materials, processing, spices used, and region of origin. One type of traditional satay is komoh. Inspired by products that can be sold in frozen processed form such as nuggets sold in frozen semi-cooked processed form, it is necessary to conduct research on satay products. The aim of this study to determine the right conditions for processed satay meat that can be stored frozen. The research method applied was an experimental method carried out in the form of treating raw satay conditions, semi-cooked satay conditions, and cooked satay conditions stored frozen. Satay was made in 2 ways, namely the traditional charcoal grilling process and the microwave grilling process. The results showed that satay komoh from Thunnus meat made with a microwave was organoleptically preferred over conventional satay komoh, both in terms of color, aroma, taste, and texture attributes. Microwave-satay has lower texture, peroxide value, Thio-barbituric Acid, and water content than conventional-satay. Satay komoh that stored frozen in half-cooked and cooked conditions is preferred over raw conditions. Satay komoh that stored frozen with increasing doneness has an effect on the texture, peroxide, Thio-barbituric Acid, and water content. The best treatment in frozen storage of satay komoh was grilling with a microwave in half-cooked conditions.